Managing and leading for science professionals (What I wish I'd known when moving up the management ladder) - Liang, Bertrand C. (Kidlington, Oxford Academic Press, 2014)
Can technical paradigms help managers lead technical companies? In Managing and Leading for Science Professionals, Bertrand Liang explains that they can, as he explores real issues of importance for technical students and managers who want to move into leadership positions. A CEO with an MBA, Liang originally trained as a neurology and oncology clinician and later earned a PhD in molecular biology and genetics. In this book, he emphasizes what he wishes he had known as he advanced through the organization. His practitioner's point of view is perfectly suited to those who are moving, or want to move, from the technical side to the business side. Focusing on the experiences of scientists and engineers, he teaches ways to speak top management's language. His insights deliver essential knowledge, empowering technical staff to succeed using the skills they know best. Describes "what I wish I'd known" as a manager with a technical background. Focuses on using skills other than risk analysis to make decisions. Explores ways to lead and manage innovation, particularly in relation to executives' responsibilities, skills, and tolerance for risk.
Includes bibliographical references and index.
Keywords: Management; Technological innovations -- Management; Electronic books